2018
DOI: 10.1007/s11060-018-2886-5
|View full text |Cite
|
Sign up to set email alerts
|

PD-1/PD-L1 and immune-related gene expression pattern in pediatric malignant brain tumors: clinical correlation with survival data in Korean population

Abstract: AT/RT, EPN, and HGG showed a relatively higher expression rate of PD-L1 (19-40%). This suggests these tumor types might be good candidates for PD-1 checkpoint blockade. We determined that gene expression may potentially serve as a molecular tool in predicting which patients will respond to immunotherapy. Further investigation is required to better understand the predictive and prognostic role of PD-L1 in pediatric brain tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 25 publications
2
15
0
1
Order By: Relevance
“…The effects of PD-L1 expression on survival in pediatric brain tumors has been recently reported by a number of groups and shows considerable variability depending on tumor type. 7,[21][22][23] Larger clinical trials are needed to further explore this relationship, as our findings did not achieve statistical significance, possibly because of the small number of patients studied or lack of uniform diagnosis.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The effects of PD-L1 expression on survival in pediatric brain tumors has been recently reported by a number of groups and shows considerable variability depending on tumor type. 7,[21][22][23] Larger clinical trials are needed to further explore this relationship, as our findings did not achieve statistical significance, possibly because of the small number of patients studied or lack of uniform diagnosis.…”
Section: Resultsmentioning
confidence: 76%
“…Nivolumab was discontinued in <6 weeks because of the radiographic evidence of disease progression in 6 patients, without making a distinction between true progression and pseudoprogression. [15][16][17][18][19][20][21][22][23][24] Five of these patients died shortly after discontinuation of the treatment, favoring true disease progression in those patients. Future studies involving checkpoint blockers should account for pseudoprogression in the disease evaluation and consider continuing the treatment despite radiographic evidence of progression early on, if patient remains clinically stable.…”
Section: Resultsmentioning
confidence: 99%
“…Recent pre-clinical evidence suggests that activation of the programmed cell death (PD-1) pathway within the tumor microenvironment plays a role in the pathogenesis of adult and pediatric high-grade gliomas [17][18][19][20][21][22]. In murine glioma models, PD-1 blockade prolongs survival and leads to durable responses [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…One study with 89 patients in Korea showed that 0% of medulloblastoma patients demonstrated expression of PD-L1 (0 out of 28 patients). 89 This was in direct contrast to other pediatric brain tumors including 40% of atypical teratoid/rhabdoid tumor (8 out of 20), 20% of ependymoma (4 out of 20), and 19% of high-grade glioma (4 out of 21) that demonstrate expression of PD-L1. This study concluded that medulloblastoma may not be a suitable candidate for PD-1 checkpoint blockade.…”
Section: Checkpoint Inhibitors In Medulloblastomamentioning
confidence: 72%